Comparative Study on Students’ Dialect of Batak Karo With Batak Toba In Speaking English - Ginting, Lastry (The Explora, 2022)
This thesis deals with dialect Batak Karo and Batak Toba. In this study the objective is identify thedialect differentiation between Batak Karo and Batak Toba when they are speaking in English and alsofind out some similarities pronunciation between BATAK Karo and Batak Toba in speaking English.This research is done through descriptive qualitative method and the data collected by observation andrecord the student when they are do conversation in speaking English. Dialect is regionally and sociallydistinctive variety of language, identified by a particular set of words and how to pronounce the word.After the data were collected then the writer identifies, analyze and categories the words. The resultindicates that there are some differences phonological. Such as when vowel /a/ said by Batak Karo is /a/and Batak Toba said /a/ become /e/ or /o/, and when Batak Toba said /e/ Batak Karo said /e/ become /i/.When vowel /e/ in English, Batak karo said by /ə/ and Batak Toba said with strong /e/. Especially forthe consonant the different is in /v/ /p/ /f/. When Batak Karo people said /v/ Batak Toba will said /p/ andBatak Toba Said /f/ Batak Karo will said /p/. It can be concluded that there are still